Effects of increasing lysine:calorie ratio and dietary fat addition on growth performance and carcass characteristics of growing-finishing barrows - M De La Llata; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1999)
A total of 1,200 growing-finishing barrows was used to determine the effects of increasing lysine:calorie ratio and dietary fat addition. Dietary treatments were arranged in a 2 x 4 factorial with two levels of fat (0 and 6%) and four lysine:calorie ratios in each of the four phases. The appropriate lysine: calorie ratios to maximize performance were: 3.01,2.25 to 2.50, 1.78 to 1.98, and 1.42 to 1.62 from 75 to 130, 130 to 175, 175 to 220, and 220 to 260 lb, respectively. These ratios equate to approximate total lysine levels of 1.00, .80, 65, and .53%, respectively, in corn-soybean meal-based diets with no added fat.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Lysine:calorie ratio; Fat; Lysine; Finishing pigs